An uncertainty quantitative model of wellbore failure risk for underground gas storage in depleted gas reservoir during the construction process. (January 2023) - Zhang, Shengyue; Shi, Lan; Jia, Delong
Abstract: The sensitivity of wellbore-wall failure risk under depleted formation-pressure coefficients and underground gas storage in depleted gas reservoirs during the construction process is quantitatively assessed, especially the failure risk of wellbore collapse and fracture in depleted reservoirs with ultralow formation-pressure coefficients, and to effectively guide safe construction. Based on the Mohr–Coulomb failure theory and multilevel confidence model, three typical in situ stress states (normal fault, slip fault, and reverse fault) are considered to establish an analytical model for wellbore-wall failure risk under different depleted reservoir pressure coefficients. Taking a depleted sandstone reservoir as the main reservoir for wellbore-wall stability analysis as an example, a wellbore-wall stability state visualization analysis model with three typical in situ stress states under arbitrary orientations and well deviation angles is obtained, and the uncertain probability distribution law of wellbore-wall collapse and fracture failure in a reservoir with an ultralow formation-pressure coefficient is constructed using a stochastic uncertainty simulation method with interval confidence. The distribution patterns of wellbore-wall stress fields and borehole safety density windows during the construction of depleted reservoirs are quantitatively analyzed. The results show that a safety density window with interval uncertainty estimates would be more intuitive for assessing the stability of the reservoir wellbore wall in a quantitative form, and it is observed that inclined well sections in depleted reservoirs typically have narrower safety density windows. In conclusion, the lower and upper limits of the safety density window in numerical examples are 1.4 to 1.6 g/cm 3 (normal fault state), 1.2 to 1.5 g/cm 3 (slip fault state), and 1.2 to 1.65 g/cm 3 (reverse fault state), respectively. The research results can provide effective guidance for wellbore instability control, design, and construction of directional wells in depleted gas reservoirs. Highlights: An uncertainty wellbore failure risk state is evaluated in a depleted gas reservoir. A multilevel interval chroma-mapping model provides a more robust quantitative basis. The ultralow formation-pressure factor has a decisive effect on wellbore failure risk. The reliability calculation approach can be used for high-risk condition identification